A new application field for BaFe12O19 used as visible light photocatalyst. (6th June 2020) - Xu, Xueli; Song, Wei
ABSTRACT: Our human being firmly believed the existing materials possessed a wider utilisation range. It was very interesting therefore that finding new application for some outdated materials. Here, the semiconductor characteristics of an old ferrite, BaFe12 O19 were explicated based on its optical properties. The direct bandgap energy was determined as 1.55 eV. The outstanding photocatalytic performance of BaFe12 O19 was confirmed by Rhodamine B (RhB) photodegradation under visible light. The RhB solution could be totally photodegraded using BaFe12 O19 powder after 3 h photocatalytic reaction. We hope this work can extend application field for BaFe12 O19, and stimulate enthusiasm for continuous study these traditional ferrites, such as, BaFe12 O19, SrFe12 O19, and ZnFe2 O4 . And we sincerely hope that the concept about new application of old materials can be extensively spread and applied.